In Dialogue: Postcolonial Theory and Intersectionality - Wallaschek, Stefan (Momentum Quarterly, 2015)
Postcolonial theory and intersectionality are the most prominent approaches in current critical social sciences. Surprisingly, both approaches have hardly talked to each other. Influenced by the German academic debate on these, I illustrate the (dis-)connecting relations of both approaches and initiate a dialogue. In a first step, I focus on the work of Chandra T. Mohanty and of Kimberlé Crenshaw. While Mohanty bases her criticism on a discourse analysis of writings about ‘Third-World-Women’ and develops a postcolonial feminist approach, Crenshaw analyzes the intersection of gender and ‘race’ and criticizes the blindness of the interconnection in court decisions in the US. I demonstrate the differences and resemblances of both approaches and argue in particular that both approaches follow a constructivist methodology which creates four nodal points for the fruitful dialogue. I illustrate this by analyzing the works of Sojourner Truth and Clara Zetkin. Both feminists focus on different categories in the triangle of ‘race’, class and gender. Through a close reading of crucial selected works, I show that Truth perceives gender and ‘race’ as equivalent forms of subordination. Zetkin, however, emphasizes the hierarchical subordination by the specific class position of women. I conclude that a closer dialogue between both theoretical perspectives can help to sharpen the view on multiple discrimination and injustice in times of neoliberal capitalist hegemony.